PENGARUH LATIHAN PUSH-UP TERHADAP KECEPATAN PUKULAN GYAKU-TSUKI CABANG OLAHRAGA KARATE PADA EKSTRAKURIKULER KARATE DI SMA KEBANGSAAN LAMPUNG SELATAN - Alfinto Kurniawan; Marta Dinata; Candra Kurniawan; Fransiskus Nurseto (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
The method used was quantitative based on experiments. The instrument used was a stopwatch. The resultsof this study showed that (1) There was a significant effect of the push-up training treatment group on the speed of Gyaku-tsuki strikes in karate extracurricular students at SMA Kebangsaan Kabupaten Lampung Selatan. With a t-test result of 5% significance (0.05), the calculated t-value was 10.555 > the table t-value = 2.145. (2) There is a significant effect of the control group or no treatment on the Gyaku-tsuki punch speed of karate extracurricular students at SMA Kebangsaan Kabupaten Lampung Selatan. With a t-test at the 5% significance level (0.05), the calculated t-value is 3.643 > the table t-value = 2.145. (3) There is a significant difference between the treatment group and the control group in terms of the speed of the Gyaku-tsuki punch among karate extracurricular students at SMA Kebangsaan Kabupaten Lampung Selatan. With a two-tailed test (significance level = 0.025), the calculated t-value is 2.101 > t-table = 2.048.